Maggot Black Soldier Fly (Hermetia illucens) Nutritional Content Using Various Culture Media - Ase Lestari; T H Wahyuni; E. Mirwandhono; N Ginting (Talenta Publisher, 2020)
Maggot BSF (black soldier fly) (Hermetia illucens) has a high crude protein content of 42.1%. The purpose of this study was to investigate the nutritional content of maggot as a substitute for fish meal by using various culture media. This research method used a completely randomized design of 5 treatments 4 replications P0 = 100% fermented rice bran, P1 = 50% fermented coconut dregs + 50% fermented rice bran, P2 = 50% fermented tofu dregs + 50% fermented rice bran, P3 = fermented rice bran 50% fermented palm kernel kernel + 50% fermented rice bran, P4 = 25% fermented coconut dregs + 25% fermented rice bran + 25% fermented tofu dregs + 25% fermented palm kernel cake. The parameters studied were moisture content, ash content, crude protein, crude fat and carbohydrates. Based on the results of the study, it was found that the use of culture media with a combination of 25% fermented rice bran + 25% fermented coconut dregs + 25% fermented tofu pulp + 25% fermented palm kernel meal was the best combination.